The French Revolution and historical materialism : selected essays - Heller, Henry (Historical materialism book series, 2017)
"This text reasserts the Marxist view of the French Revolution as a bourgeois and capitalist revolution. Based mainly on articles published in the journal Historical Materialism it challenges the still dominant revisionist view of the French Revolution. It serves to restore the close tie between the history of the Old Regime and the Revolution. It demonstrates that the rise of a bourgeois capitalist class has a long history dating back to the sixteenth century. Moreover, it shows that the Revolution itself played a large role in strengthening the bourgeoisie politically and economically while bringing about the unification of financial and productive capital. Indeed, it shows that the rising of the masses during the Revolution, viewed by revisionism as economically regressive, in fact helped to bring about the consolidation of capitalism"--Publisher description.